Smaller household size and higher prevalence of serious psychological distress in younger people and never-married people: a nationwide cross-sectional survey in Japan - Tomioka, Kimiko; Shima, Midori; Saeki, Keigo (Frontiers in Public Health, 2024)
Background Small-member households are increasing worldwide. However, most previous studies have focused on older people and living alone. Using the latest national survey data, we investigated a dose–response relationship between household size and serious psychological distress (SPD). Methods We analyzed data from the 2019 Comprehensive Survey of Living Conditions in Japan. The study participants were 405,560 community-dwelling adults aged 20 or older. Household size was classified into 5 or more, 3 or 4, two, and one (i.e., living alone). SPD was defined as ≥13 points based on the Kessler 6-item Psychological Distress Scale. We used multivariable logistic regressions and included age, education, equivalent household expenditures, housing tenure, employment contract, smoking, and illness under treatment as covariates. Results After stratified analyses by age and gender, a dose–response relationship between smaller household size and more common SPD was significant for younger, but not for older people (p-trend was <0.001 in men aged 20–59 and women aged 20–39). After stratified analyses by gender and marital status, a dose–response relationship was significant only for the never-married group in both genders (p-trend was <0.001 in never-married men and women). Conclusion Smaller households were associated with higher prevalence of SPD in younger adults and in never-married individuals, regardless of gender. Our findings suggest a need to focus on younger people and never-married people to reduce the mental health risks due to small household sizes.